Prevalence of complications and health seeking behaviour of patients with type 2 diabetes mellitus: a community based study - Sekhar, Maddigalla Chandra; Sekhar, Chittooru Chandra (International Journal Of Community Medicine And Public Health, 2023)
Background: Diabetes mellitus is a chronic disease with a variety of micro-and macro-vascular complications. Health seeking behaviour is directly related to occurrence of diabetes complications by identifying them early and to plan diabetes care and management upon diagnosis. So, this study was planned to know the prevalence of complications in Type 2 diabetes mellitus patients and their level of treatment seeking behaviour. Methods: A total of 75 type 2 DM patients from rural area were studied. Patients were selected by taking 8 villages as strata and minimum of 9 patients were selected from each village. Patients were interviewed face-to-face for knowing details related to diabetes, and its complications and about health seeking behaviour. Results: Around 21.3% patients had complications related to diabetes mellitus, in which peripheral neuropathy was most common. As many as 45% patients seeking care from govt. facility and 60% patients seeking care from Pvt. facility had poor health seeking behaviour. Significantly higher number of patients seeking health care from Pvt. facility (77.8%) having poor health seeking behaviour had complications than patients seeking health care from govt. facility (33.3%). Odds of having complications was 7 times higher for patients seeking health care from Pvt. facility than for patients approaching govt. facility. Conclusions: Good health seeking behaviour is needed to improve the quality of life of patients suffering with type 2 DM.